Analysis of the Final Match of Pon XXI Sepak Takraw Double Event Men North Sumatra vs Aceh - Mawardinur, Mawardinur (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2025)
Match result analysis needs to be done to see the advantages and disadvantages in more detail regarding the ability to play sepak takraw double event North Sumatra vs Aceh. The purpose of this study was to determine the playing skills of North Sumatra and Aceh. Therefore, it is necessary to analyze the match results as a basis for evaluating the team’s abilities. The method used in this study is the survey method by observing and analyzing the match results. The results of the analysis provide a description of the ability to compete in a team match Double event Men’s in smash skills North Sumatra managed to get 26 times with a percentage of 78.79% and Aceh managed to get 25 times with a percentage of 73.53. In block skills, the North Sumatra team got 1 result with a percentage of 4.76 while the Aceh team managed to get 3 times with a percentage of 11.54. In serve skills, the North Sumatra team managed to get 37 with a percentage of 82.22 while the Aceh team managed to get 36 times with a percentage of 81.82%. In the receive skill, the North Sumatra team managed to get 32 times with a percentage of 88.89% while the Aceh double team managed to get 36 times with a percentage of 97.30%. The conclusion between the two teams is that the North Sumatra team has an advantage in the smash and serve technique with a percentage of 3.66% while the Aceh team has an advantage in the block and receive technique with a percentage of 15.19%, the most frequent success between the two teams is smash, serve and receive. The failure that often occurs between the two teams is block.